Analysis of Islamic Law on Sharia Economic Disputes (Studies UU No.3/2006 and UU No.50/2009) - Muhammadong, Muhammadong (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The emergence of sharia economic disputes cannot be separated from differences in interpretation of the sharia understanding of contractual transactions. Default arises because there is a breach of agreement between the two parties so that they cannot find a solution. Islamic law exists to provide solutions to economic problems that occur, either through courts or without courts. The birth of Law no. 3 of 2006 wants to emphasize the function of religious courts in sharia economic disputes without conflicting with Law no. 50 of 2009 concerning disputes faced by not a Muslim. Sharia economic disputes faced so far can be returned to applicable Islamic law.